Breast cancer survival in Ethiopia: A cohort study of 1, 070 women. Issue 3 (10th January 2014) - Kantelhardt, E.J.; Zerche, P.; Mathewos, A.; Trocchi, P.; Addissie, A.; Aynalem, A.; Wondemagegnehu, T.; Ersumo, T.; Reeler, A.; Yonas, B.; Tinsae, M.; Gemechu, T.; et al.
<x xml:space="preserve">Abstract</x> There is little information on breast cancer (BC) survival in Ethiopia and other parts of sub‐Saharan Africa. Our study estimated cumulative probabilities of distant metastasis‐free survival (MFS) in patients at Addis Ababa (AA) University Radiotherapy Center, the only public oncologic institution in Ethiopia. We analyzed 1, 070 females with BC stage 1–3 seen in 2005–2010. Patients underwent regular follow‐up; estrogen receptor‐positive and ‐unknown patients received free endocrine treatment (an independent project funded by AstraZeneca Ltd. and facilitated by the Axios Foundation). The primary endpoint was distant metastasis. Sensitivity analysis (worst‐case scenario) assumed that patients with incomplete follow‐up had events 3 months after the last appointment. The median age was 43.0 (20–88) years. The median tumor size was 4.96 cm [standard deviation (SD) 2.81 cm; n = 709 information available]. Stages 1, 2 and 3 represented 4, 25 and 71%, respectively (n = 644). Ductal carcinoma predominated (79.2%, n = 1, 070) as well as grade 2 tumors (57%, n = 509). Median follow‐up was 23.1 (0–65.6) months, during which 285 women developed metastases. MFS after 2 years was 74% (69–79%), declining to 59% (53–64%) in the worst‐case scenario. Patients with early stage (1–2) showed better MFS than patients with stage 3 (85 and 66%, respectively). The 5‐year MFS was 72% for stages 1 and 2 and 33% for stage 3. We present a first overview on MFS in a large cohort of female BC patients (1, 070 patients) from sub‐Saharan Africa. Young age and advanced stage were associated with poor outcome.